Backlash Analysis of Gear Transmission of Parallel Uniform Planetary Gear - Guo Jing; Zhu Zengbao; Liu Chun; Zhang Biao (Jixie chuandong, 2018)
Based on the NGW planetary gear transmission system,a gear transmission of parallel uniform planetary gear is proposed to reduce the transmission error of asteroid transmission system and improve its transmission accuracy. The backlash formula is obtained by considering the influence of gear eccentricity error and working load on the backlash of planetary transmission system. The influence of load and gear eccentricity error on the transmission system is analyzed. The results show that,as the working load increasing,the backlash of gear transmission of parallel Uniform Planetary gear and NGW planetary gear transmission system are all increased. But the backlash of NGW planetary gear transmission system is slightly larger. Under the condition of same gear eccentricity error,the backlash of gear transmission of parallel uniform planetary gear is less than the backlash of NGW planetary gear transmission system. In the gear transmission of parallel uniform planetary gear,the eccentricity error of the solar wheel has a great impact on the transmission system,but the eccentricity error of the outer ring has less influence on the transmission system. The influence of planetary wheel eccentricity error on the transmission system is between sun wheel and planet gear.